Stability study and development of the validated infrared spectrometric method for quantitative analysis of sevoflurane compared with the gas chromatographic method - Kahtan Jassim Hasson (Wolters Kluwer Medknow Publications, 2024)
Sevoflurane, also called fluoromethyl ether, is an inhalation anesthetic agent used to initiate and maintain general anesthesia for adults and pediatric patients during surgical procedures. Several analytical methods have previously been applied to follow the properties and quality of sevoflurane, including mass spectrometry and gas chromatography methods. These methods are practically tedious and need sophisticated apparatus. In the present work, an attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectrometric method was used for the quantitative determination of sevoflurane which is characterized as a fast, accurate, and available technique for most pharmaceutical laboratories, besides the gas chromatographic method which is the most suitable for the detection of impurities. Sevoflurane is a liquid and it is applied directly on the glass top of the ATR-FTIR either as a concentrated solution or diluted with hexane as a diluent, which did not interfere with sample determination within the specified wavelength range of the IR spectrum, particularly the wavelength of the ethereal group at 1200 cm−1. This method can be applied to the identification test and quantitative assay of sevoflurane since it is validated for the precision, accuracy, reproducibility, and specificity in the analysis of sevoflurane as a pharmaceutical product. However, still, there is a need for a gas chromatographic method to detect the impurities and degradation products during the stability study of sevoflurane.